Impact of Covid-19 On Indonesia's Economy - Novia Putri Mauluddiyah; Habib Adjie (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
This study aims to determine the impact of Covid-19 on the current Indonesian economy and this type of research is a type of data analysis research library, data reduction, data display and verification / conclusion the results of this study indicate the impact of Covid-19 on the Indonesian economy today with various the impact on the economy due to the Covid-19 pandemic that occurred at this time it is necessary to know the impacts that occur namely the difficulty in finding employment, hard to meet the needs of daily life and also do not have income to meet the needs for a day and many troubles were received from all sectors of the economy in all sectors and also felt the effects of Covid-19.